S13-2: Adapting and Implementing Physical Literacy Tools for Ukrainian Youth: Bridging Global Standards With Local Context (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: To adapt the Canadian Assessment of Physical Literacy (CAPL, version 2) protocol and assess the validity of its affective and cognitive domains. Integrating a physical literacy (PL) approach offers a strategic method for promoting sustainable health practices among youth. A key step in advancing studies in this area is adapting tools to assess PL. However, PL remains a relatively new concept in Ukraine in terms of policy, research, and practice, emphasising the need to develop local expertise during the adaptation process to ensure that the tools are relevant to unique cultural, societal, and educational context.Methods: The study followed the guidelines outlined in the Consensus-Based Standards for the Selection of Health Status Measurement Instruments. A group of experts (n = 22) who had previously participated in organised training courses on PL assessed the content validity. The psychometric properties of the Motivation and Confidence, and Knowledge and Understanding components of the CAPL protocol were evaluated using a sample of schoolchildren aged 9–12 years (n = 426).Results: After a four-step translation process, the CAPL protocol was analysed by Ukrainian experts in physical education and pedagogy. The Ukrainian version demonstrated sufficient content validity. According to the experts, the proposed question blocks related to the affective and cognitive components of PL were clear and well-formulated. Some difficulties arose when assigning certain content blocks to specific sections of the protocol. The Ukrainian version of CAPL demonstrated acceptable validity, internal consistency of scales, and test-retest reliability, confirming its applicability for children aged 9–12 years.Conclusions: Promoting and implementing PL requires a comprehensive approach. This involves developing appropriate tools and simultaneously building expertise among local specialists to ensure effective assessment, proper tool administration, and accurate interpretation of results. Involving local experts in adapting and validating PL tools ensures they are culturally relevant and empowers professionals in physical education, sports, and pedagogy. This, in turn, enhances their ability to promote PL and improve health outcomes, supporting efforts to integrate PL into national strategies, educational reforms, and public health initiatives aimed at increasing youth physical activity.Support/Funding Source: The author received no financial support for the research.Keywords: Children, physical literacy, health practices, tools, adaptation